Integrated Analysis of the Functions and Prognostic Values of RNA-Binding Proteins in Colorectal Cancer - Wang, Ya; Chen, Yuqiao; Xiao, Shuai; Fu, Kai (Frontiers in Cell and Developmental Biology, 2020)
Colorectal cancer (CRC) is one of the most common malignant tumors. Selecting effective treatment for CRC patients, especially in the early stages, remains a challenge due to the lack of adequate biomarkers. Recent evidence suggests that RNA binding proteins (RBPs) play a vital role in development and progression of carcinogenesis. However, their mechanisms in cancer progression are still limited. The role of RBPs in CRC have been poorly understood. 1542 reported RBPs were analyzed between CRC tissues and normal tissues using the Wilcox test to identify differentially expressed RBPs (DE RBPs). Then the potential functions and the prognostic value of these DE RBPs was explored through a systematic bioinformatics analysis. 177 DE RBPs were identified between CRC tissues and normal tissues. A protein-protein interaction (PPI) network was constructed based on DE RBPs, and critical modules were screened. A regulatory network between prognostic DE RBPs and differentially expressed transcription factors (DE TFs) was constructed. Besides, a risk signature was built based on prognostic DE RBPs, which is able to predict overall survival of CRC patients with high accuracy. In conclusion, the results provided a comprehensive understanding of the functions of RBPs in CRC, as well as an RBP-related prognostic signature.